PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN MENGGUNAKAN PENDEKATAN DISCOVERY DI KELAS IV SD - Suryan, Len (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The research was conducted because of low science learning result in the fourth grade of Elementary School 31 Batang Barus Solok, and a classroom action research (CAR), consists of two cycles, four stages: planning, implementation, observation and reflection. This study is using Discovery Approach. It showed an increase in learning result, cycle I 68.43, second cycle of 77.62. So it can improve learning outcomes Fourth grade students of Elementary School 31 Batang Barus Solok. Kata Kunci: pembelajaran IPA, pendekatan discovery